Tunability of Band Gap and Photoluminescence in CH3NH3PbI3 Films by Anodized Aluminum Oxide Templates - Zhan Zhang (Nature Portfolio, 2017)
Abstract Hybrid organic-inorganic halide CH3NH3PbI3 perovskite films are deposited on anodized aluminum oxide templates with the different pore diameters via one-step spin coating method. The obvious 0.082 eV blue shift of optical band gap is observed in films with decreasing the diameters of pores from 400 to 30 nm. And numerical simulations based on finite element modeling are carried out to represent the absorption edge and consistent with the experiment results. It is interesting that the films show the intense photoluminescence with the excitation intensity of less than 1 μW. Moreover, the photoluminescence intensity is increased with increasing pore diameters, which is attributed to the radiative recombination rate of photogenerated electrons and holes. These results pave a way for the further understanding of tunable photophysical properties of perovskite films.